Power and culture in supply chains: contributions of the strategic action fields approach - Silvio Eduardo Alvarez Candido; Fernanda Veríssimo Soulé; Mário Sacomano Neto (Production)
Abstract Important research efforts have been developed to account for power in the analysis of supply chains. This paper argues that further gains may arise by considering organizations as social constructions mediated not only by power relations, but also by cultural representations intrinsically intertwined to it. Its purpose is to discuss the dynamics of stability and change in supply chains based on the Strategic Action Fields (SAFs) approach. A theoretical essay was elaborated discussing some of the main implications of this perspective to the study of supply chains and presenting propositions to enable the construction of research objects and guide empirical studies in the area. Propositions emphasize how ongoing cultural-political relations circumscribed to different fields, including the organization, with its internal disputes.